Methane emissions from paddy fields: a root-to-shoot perspective on rice plant traits: Rice plant traits regualting methane emissions - Yadav, Arvind; Kumar, Anjani; Deuri, Bikramjit; Mohanty, Sangeeta; Sahu, Abhishek Kumar; Patra, Sriman Smrutiranjan; Behera, Biswajit; Biswal, Rajendra; Mahapatra, Abhishek; Raj, Bhuvnesh (ORYZA-An International Journal of Rice, 2025)
Methane (CH4) emissions from flooded rice paddies are a major source of global greenhouse gases (GHGs), especially in rice-dominant countries such as India and China. With rising global rice demand, it is critical to adopt sustainable cultivation practices that reduce environmental impacts while safeguarding food security. This review highlights the morpho-physiological traits regulating CH4 formation and transport from soil to atmosphere, focusing on root and shoot anatomical features, carbon allocation patterns, aerenchyma-mediated gas flow, root exudate composition, and the indirect influence of panicle architecture on carbon partitioning. Key traits such as restricted aerenchyma development, optimized radial oxygen loss (ROL), improved shoot sink strength, and modified root exudation profiles emerge as promising targets for mitigation. The review also explores the interplay between microbial methanogenesis, plant anatomy, and gas exchange. Integrating these biological insights with agronomic best practices can accelerate the development of climate-smart, high-yielding rice cultivars that contribute to low-carbon agriculture.